Assessment of myocardial sympathetic innervation with [123I]mIBG myocardial scintigraphy : A comparative study between an Anger and a ring-configured cadmium-zinc-telluride gamma camera - Hagerman, Jessica; Engblom, Shahnaz Akil; Andelius, Irma Cerić; Stenvall, Anna; Minarik, David; Hall, Sara; Stomrud, Erik ; 0000-0002-0841-5580; Nahimi, Adjmal; Smith, Ruben; Hansson, Oskar ; 0000-0001-8467-7286; Hedeer, Fredrik (Journal of Nuclear Cardiology, 2025)
Background Assessment of myocardial sympathetic innervation with iodine-123-metaiodobenzylguanidine ([123I]mIBG) scintigraphy is conventionally performed by determining the heart-to-mediastinum ratio (HMR) on planar images. This study aimed to investigate the feasibility of determining HMR from reprojected [123I]mIBG planar images derived from tomographic data by a ring-configured cadmium-zinc-telluride (CZT) gamma camera and its agreement with HMR determined from [123I]mIBG planar images by an Anger gamma camera, in the assessment of myocardial sympathetic innervation. Methods A total of 105 study participants (suspected idiopathic rapid-eye-movement sleep behavior disorder n = 55, early-stage Parkinson's Disease n = 36, and healthy controls n = 14) who were referred for [123I]mIBG myocardial scintigraphy were included, in addition to eight phantom experiments simulating a range of HMR. HMR was determined from planar and reprojected planar images acquired with an Anger gamma camera and a ring-configured CZT gamma camera, respectively, for all study participants and phantom experiments. Agreement in HMR between the two imaging methods was analyzed in Bland-Altman plots. Intra- and interobserver variability was evaluated for both imaging methods in a subset of images. Results The agreement between planar and reprojected planar images was good, with a mean difference in HMR of 0.11 (95% limits of agreement −0.16 to 0.38) for the study participants. Intra- and interobserver variability was low and comparable for both imaging methods. Results from the phantom experiments were consistent with those from the study participants. Conclusions Determining HMR from reprojected [123I]mIBG myocardial scintigraphy planar images acquired with a ring-configured CZT gamma camera is feasible and shows good agreement with HMR determined from planar images by a conventional Anger gamma camera.
Keywords: CZT; Heart-to-mediastinum ratio; Iodine-123-metaiodobenzylguanidine; Myocardial sympathetic innervation; Reprojected planar images; Ring-configured; StarGuide; [I]mIBG